Sorsby's fundus dystrophy in the British Isles: demonstration of a striking founder effect by microsatellite-generated haplotypes. - Wijesuriya, S D; Evans, K; Jay, M R; Davison, C; Weber, B H; Bird, A C; Bhattacharya, S S; Gregory, C Y (Genome Research, 1996)
Sorsby's fundus dystrophy (SFD) has been mapped to a genetic interval of 8 cM between loci D22S275 and D22S278. A total of 15 families, unrelated on the basis of genealogy and expressing the SFD phenotype were identified from a large data base of genetic eye disease families originating from diverse parts of the British Isles. The identification of the same Ser181Cys mutation cosegregating with disease in each family led us to consider the hypothesis of a founder effect being present. In all families studied, the same relatively infrequent allele (occurring in just 11% of the control group) was associated with disease at marker locus D22S280. A highly significant disease-associated haplotype, spanning across 3 cM of the SFD locus, was conserved in 11 of the 15 families (68% of all affected chromosomes); a further extended haplotype spanning up to 7 cM, was identified in 5 families (27% of SFD-associated chromosomes) and possibly represents the ancestral haplotype. This haplotype analysis has refined the TIMP3 gene localization to a 1- to 3-cM interval between marker loci D22S273 and D22S281 and provides strong evidence for a single mutational event being responsible for the majority of SFD identified in the British Isles.